KRIRIS AKHLAK DAN SOSIAL PADA SISWA SEKOLAH DASAR DALAM PERSPEKTIF PENDIDIKAN AGAMA ISLAM - Sarah Auliyah Nst; Sri Handayani; Laswardi Laswardi; Khoirunnisaiyah Lubis (Universitas Muhammadiyah Tapanuli Selatan, 2025)
The moral and social crisis in elementary school students is a serious concern in the world of education. Attitudes such as disrespectful behavior towards parents and teachers, bullying cases, and low social empathy reflect moral degradation that requires deep handling. This article aims to analyze the causes of the moral and social crisis in elementary school children and offer solutions through the Islamic Religious Education (PAI) approach. This study uses a qualitative approach with literature analysis and observation methods, identifying factors such as changes in family parenting, the influence of the social environment, and the lack of moral learning in schools. The results of the study show that the PAI approach, through the cultivation of monotheistic values, noble moral education, and role modeling, can be a strategic solution to build moral and empathetic children's character. In addition, collaboration between schools, parents, and the community is an important key in instilling moral values consistently. This article recommends strengthening the PAI curriculum, teacher training, and the use of positive technology as concrete steps in overcoming the moral and social crisis. Thus, Islamic religious education has a central role in shaping a moral, inclusive, and competitive generation in the modern era.